Preventive effect of Silibinin in combination with Pu-erh tea extract on non-alcoholic fatty liver disease in ob/ob mice. Issue 3 (6th February 2017) - Hu, Wen-Yi; Ma, Xiao-Hui; Zhou, Wang-Yi; Li, Xin-Xin; Sun, Ting-Ting; Sun, He
Abstract : This study investigates the synergistic effect of Silibinin combined with Pu-erh tea extract against NAFLD. Abstract : There are presently no miracle drugs for non-alcoholic fatty liver disease (NAFLD). This study investigates the synergistic effect of Silibinin combined with Pu-erh tea extract (PTE) against NAFLD and explores the suggested mechanism of action. Ob/ob mice were fed a high fat diet along with the oral administration of Silibinin (86 mg per kg per day), PTE (250 mg per kg per day) or their combination for 6 weeks. Their lean littermates who were fed with standard chow diet were used as the control group. The blood biochemical index and histopathological evaluation were analyzed. The expression of genes involved in the lipogenesis pathway and cholesterol metabolism were evaluated. When compared with that of the NAFLD group, the body weight and blood lipid of the mice from the PTE group or combination group were significantly reduced. To some degree, fat metabolism and the inflammatory response were ameliorated by Silibinin and PTE used alone or in combination. It was notable that the combination group had a stronger efficacy in adjusting fat metabolism and inhibiting oxidative stress than that of Silibinin or PTE used alone. Silibinin and PTE inhibited fat synthesis by regulating the mRNA expression of CRTC2, SREBP-1c, and SCD-1. Moreover, the cholesterol homeostasis was improved in the treatment groups via regulating the mRNA expression of ABCA1 and ApoB100. The improvement of the combination group was superior to each drug used alone. In conclusion, Silibinin in combination with PTE can prevent NAFLD with greater potential than Silibinin or PTE used alone and may be a new therapeutic strategy.